Mixed-valence realizations of quantum dot cellular automata. (June 2023) - Macrae, Roderick M.
Abstract: This article reviews recent progress in the design and theoretical investigation of molecular implementations of quantum-dot cellular automata (QCA) for field-coupled nanocomputing applications. QCA is a classical computing paradigm based on Coulombic quantum interactions between nanoscale subunits consisting of two or more quantum dots. Shrinking these dots to the molecular scale maximizes device density and permits operation at ambient temperatures. The essential feature of molecular QCA systems is the presence of two or more coupled redox centers separated by spacers. In this work candidate systems ranging from simple organic molecules to self-assembled multi-center mixed-valence organometallic complexes are surveyed, and some of the challenges remaining to be faced both in theoretical understanding and practical implementation are discussed.